Transformative higher education: Critical to the success of self-reliant India - Patel, B .K. (University News)
Indian higher education system has come a long way since the establishment of its first university in 1857. The system has grown in size and complexity, with more than 1000 universities and over 50,000 colleges catering to the diverse educational needs of the country. However, there is a pressing need for transformation to meet the challenges of a rapidly changing world, and to support the vision of a selfreliant India or Atma Nirbhar Bharat.- Reproduced